2021
DOI: 10.18016/ksutarimdoga.vi.770817
|View full text |Cite
|
Sign up to set email alerts
|

Doğrusal Olmayan Temel Bileşenler Analizinin Tanıtımı ve Uygulanabilirliği

Abstract: Nonlinear principal component analysis (NLPCA) is a descriptive dimension reduction method that examines the relationships between variables and displays the results numerically and visually in multivariate datasets that have a linear or nonlinear relationship between them. In this study, it was aimed to present the basic explanatory information about nonlinear principal components analysis (NLPCA) and to emphasize its usability by performing application. In the study, data obtained from 270 samples for 17 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…This demonstrates the complex effects of different factors on plant growth. Furthermore, these analyses can help in the summarization and interpretation of variables (Demir et al, 2021). Yavuz et al (2020) also found that PCA is a useful technique to assess sensitivity to stressful conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrates the complex effects of different factors on plant growth. Furthermore, these analyses can help in the summarization and interpretation of variables (Demir et al, 2021). Yavuz et al (2020) also found that PCA is a useful technique to assess sensitivity to stressful conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Bu bağlamda, Kategorik temel bileşenler analizi ön plana çıkmaktadır. 10 Kategorik temel bileşenler analizi, geometrik olarak ele alındığında, gerçek uzay yerine daha düşük boyutlu bir uzayda değişken ve kategorileri arasındaki ilişkileri grafiksel olarak göstermeyi amaçlamaktadır. Diğer bir ifade ile yöntem, sayısal dönüşümler yaparak, X'in nesne skorlarını bulmayı ve Yj'nin bir dizisini çeşitli yollarla kısıtlayarak minimize etmeyi amaçlamaktadır.…”
Section: Yöntemunclassified